Why there should be no argument from evil: remarks on recognition, antitheodicy, and impossible forgiveness - Pihlström, Sami (International journal of philosophy and theology, 2017)
I argue that we should emancipate the problem of evil and suffering from theodicist assumptions that lead to a chronic non-acknowledgment of the sufferers’ experiential point of view. This also entails emancipating the problem of evil and suffering from the need to consider the so-called argument from evil. In the argument ‘from’ evil, evil and suffering are seen as pieces of empirical evidence against theism. This presupposes understanding theism as a hypothesis to be tested in an evidentialist game of argumentation. Such a presupposition already fails to acknowledge the depth and variety of both religious and nonreligious approaches to living with evil and suffering. One way of cashing out what moral antitheodicism amounts to is to analyze theodicism as a failure of recognizing others’ suffering. Furthermore, one way of cashing out what this mis- or nonrecognition amounts to is to analyze the unforgivability of evil. Focusing on recognition and forgiveness here can be understood as an attempt to show that there is something seriously wrong with mainstream analytic philosophers’ of religion preoccupation with the argument from evil. In contrast, an ethically proper response to evil and suffering emerges from a serious consideration of recognition, forgiveness, and the unforgivable.